Evaluation of Inoculum Addition To Stimulate In Situ Bioremediation of Oily-Sludge-Contaminated Soil - Mishra, Sanjeet (American Society for Microbiology, 2001)
A full-scale study evaluating an inoculum addition to stimulate in situ bioremediation of oily-sludge-contaminated soil was conducted at an oil refinery where the indigenous population of hydrocarbon-degrading bacteria in the soil was very low (10(3) to 10(4) CFU/g of soil). A feasibility study was conducted prior to the full-scale bioremediation study. In this feasibility study, out of six treatments, the application of a bacterial consortium and nutrients resulted in maximum biodegradation of total petroleum hydrocarbon (TPH) in 120 days. Therefore, this treatment was selected for the full-scale study. In the full-scale study, plots A and B were treated with a bacterial consortium and nutrients, which resulted in 92.0 and 89.7% removal of TPH, respectively, in 1 year, compared to 14.0% removal of TPH in the control plot C. In plot A, the alkane fraction of TPH was reduced by 94.2%, the aromatic fraction of TPH was reduced by 91.9%, and NSO (nitrogen-, sulfur-, and oxygen-containing compound) and asphaltene fractions of TPH were reduced by 85.2% in 1 year. Similarly, in plot B the degradation of alkane, aromatic, and NSO plus asphaltene fractions of TPH was 95.1, 94.8, and 63.5%, respectively, in 345 days. However, in plot C, removal of alkane (17.3%), aromatic (12.9%), and NSO plus asphaltene (5.8%) fractions was much less. The population of introduced Acinetobacter baumannii strains in plots A and B was stable even after 1 year. Physical and chemical properties of the soil at the bioremediation site improved significantly in 1 year.